Disposition in the Implementation of the Dhuha Prayer Policy in Madrasah Tsanawiyah (Universitas Muhammadiyah Sidoarjo, 2017)
One thing that is important in shaping the students who berakh lakul karimah is by providing character education to students. One of the policies made to shape the character of learners is by making a dhuha prayer policy in congregation. This study aims to find out how the implementation of dhuha prayer policy. The research method used is descriptive qualitative approach with case study research type. The study was conducted in Mts. Al-Amien Kediri. Data collection techniques used are through observation, interviews, documentation Data analysis techniques used are data reduction (brand data / summarize data), display data (presentation data), and withdrawal of verification conclusions. Validity of data used is with triangulation and peers. The results of this study indicate that, dhuha prayer policy in Mts. Al-Amien Kediri is implemented through one component of disposition or attitude, where in this disposition component includes 3 things: first, the commitment that the dhuha prayer is held because of the implementation of the curriculum 13, the two excellent student responses, and the student's understanding about the privilege of prayer dhuha.